Welding distortion prediction and mitigation in thick steel plate structures on ships. (2nd December 2022) - Cao, Yu; Song, Yuze; Liu, Ziyan; Wu, Taifeng; Bai, Yong
ABSTRACT: In the ship fabrication process, welding distortion will affect the dimension accuracy. In this paper, an industrialisation prediction method for thick steel plate structures on ships is proposed based on a combination of thermal-elastic-plastic finite element method and inherent deformation theory to reduce the welding distortion in the design stage, and its applicability is verified through a comparison of measurements in the shipyard and numerical simulations. The thick plate models produced by multi-pass welding technology are selected to analyse the welding distortion. The results show that the numerical prediction results are in good agreement with the measurement on site. The transverse bending distortion is the main factor that affects the fabrication accuracy. To mitigate welding distortion, the influence of welding sequence and flame heating is examined. This research may provide a macro concept for understanding the distribution characteristics of welding distortion and serve as a mitigation reference for manufacturing engineers.